Challenges in developing materials for microreactors: A case-study of yttrium dihydride in extreme conditions - Tunes, M.A.; Parkison, D.; Huang, Y.; Chancey, M.R.; Vogel, S.C.; Mehta, V.K.; Torrez, M.A.; Luther, E.P.; Valdez, J.A.; Wang, Y.; Yu, J.; Cinbiz, M.N.; et al. (Acta materialia, 2024)
The development of microreactor technology presents an efficient solution for providing portable electricity, catering to both human space exploration needs within our solar system and supplying power to remote Earth-bound areas. The miniaturization of nuclear reactors poses immediate new challenges for materials science with respect to the capability for controlling nuclear reactions via thermalization of highly-energetic neutrons. In a microreactor, neutron moderation takes place in compact geometries, thus new moderator materials are required to exhibit high moderating power per unit of volume. This challenge is currently being addressed through the development of transition metal hydrides, known for their strong nuclear moderation capability but to date, research on their irradiation response is limited, specifically regarding phase stability, hydrogen in-lattice retention, and their dependence on irradiation temperature and dose. Herein, we present a detailed investigation on the response of yttrium dihydride (YH2) to heavy ion irradiation. The experiments indicate that YH2 is stable up to an irradiation dose of 2 dpa and below 800°C, identified herein as a critical temperature for YH2. Our study detected the nucleation and growth of voids as a function of the irradiation temperature. They were the predominant type of radiation damage present in the microstructure of YH2 that was distinguishable from pre-existing defects in the pristine YH2 samples. Below the critical temperature, no phase transformation (degassing/dehydriding) nor amorphization occurred. Experimental results with concomitant density functional theory calculations allowed us to elaborate and propose new strategies to enhance the metal hydride performance in extreme environments. [Display omitted]